Comparative Analysis Of Water Network Demand And Development With The Availability Of Clean Water In The Regional Drinking Water Company (RDWC) Lematang Enim - Diki Ernando; Heni Fitriani; Febrian Hadinata (Green Publisher Indonesia, 2024)
This study aims to analyze the projected demand for clean water and assess the existing condition of the clean water network in relation to the projected population growth in the next 10 years; Analyze the availability of water discharge from the Lematang Enim RDWC water source in meeting those needs; Analyze the development of clean water distribution networks. This research was conducted from August to December 2023. The research location is in Gelumbang Subdistrict, Muara Enim Regency. Data were collected through interviews using questionnaires related to performance, availability, and distribution of water. The results of the study show that the water demand from projection results increases every year from 2022 to 2041; the availability of water from the Lematang River is still sufficient for drinking water needs; The water needs of Gelumbang sub-district in 2032 from the calculation results obtained domestic needs of 165,403.6 m3/day, Non-domestic needs of 419.68 m3/day, and water loss of 33,164.656 m3/day; The total demand for discharge over the next 10 years (2022-2032) to meet 413,731 SL is 198,987.936 m3/day. Thus, there is an increase in the number of customers from 2022-2032 by 113,348 so that the additional distribution network needed by the Lematang Enim RDWC to meet the discharge is 45,339.2 m3/day from 2023 to 2032, totaling 113,348 so that the additional distribution network needed by the Lematang Enim RDWC to meet the discharge is 45,339.2 m3 from 2023 to 2032.